A comparative analysis of 'good citizenship': A latent class analysis of adolescents' citizenship norms in 38 countries. Issue 1 (January 2016) - Hooghe, Marc; Oser, Jennifer; Marien, Sofie
Various authors have claimed that citizenship norms have changed dramatically in contemporary societies. Recent research has studied the implications of Russell Dalton's argument that duty-based citizenship norms (emphasizing voting and obeying the law) are being replaced by engaged citizenship norms (emphasizing self-expressive and non-institutionalized forms of participation). In this article we use the 2009 International Civic and Citizenship Education Survey ( n =140, 650) to ascertain the cross-national empirical validity of engaged and duty-based norms. By means of latent class analysis, we show that both of these citizenship norms are indeed adhered to by different groups of adolescents. We also show, however, that only half of the research population holds these two norms, while other more traditional norms are also identified. The findings confirm expectations that high-status respondents with low political trust are more likely to adhere to engaged norms, but the country-level findings contradict expectations: engaged norms are less prevalent in highly developed stable democracies, and this casts doubts on the hypothesis that new engaged citizenship norms are predominantly found in stable highly developed democracies.